Migrants' Self-Selection and the Vicious Circle of Right-Wing Populism - Frédéric Docquier; Chrysovalantis Vasilakis (Institute of Labor Economics (IZA), 2024)
We test whether the level of right-wing populism in a given country influences the size and skill composition of its immigration and emigration flows. To do so, we use an instrumental variable approach, where we instrument variations in right-wing populism using a combination of collective memory, represented by the average vote share of right-wing parties between 1900 and 1950, and trigger variables, such as economic insecurity shocks. Our results show that an increase in right-wing populism leads to a decrease in the inflow of college-educated migrants, and this relationship is twice as strong as the effect on the inflow of low-skilled migrants. To a lesser extent, we also find that right-wing populism leads to an increase in high-skilled emigration, while leaving low-skilled emigration unaffected. These effects are not necessarily associated with the election of a populist government or stricter migration policies, suggesting that both in- and out-migration decisions may be influenced by the broader political climate and prevailing voter attitudes. As a result, right-wing populism tends to lower the average educational attainment of both immigrants and left-behind voters, which helps explain the persistence of right-wing populism despite its proven negative impact on the economy.
Keywords: D72; F22; F52; 330; immigration; emigration; selection; right-wing populism